2017
DOI: 10.1259/dmfr.20160268
|View full text |Cite
|
Sign up to set email alerts
|

High isotropic resolution magnetic resonance imaging of the mandibular canal at 1.5 T: a comparison of gradient and spin echo sequences

Abstract: Objectives: The precision of localizing the mandibular canal prior to surgical intervention depends on the achievable resolution, whereas identification of the nerve depends on the image contrast. In our study, we developed new protocols based on gradient and spin echo sequences. The results from both sequences were quantitatively compared for their agreement to identify the most suitable approach. Methods: By limiting the field of view to one side of the mandible, three-dimensional acquisitions with T 1 weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…More recent studies showed an accurate and high‐resolution display of the inferior alveolar nerve and intraoral anatomy within clinically feasible scanning times using specific surface coils and the interference of dental implants and inferior alveolar nerve using MRI (Flügge et al, 2016; Gradl et al, 2017; Kreutner et al, 2017; Wanner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed an accurate and high‐resolution display of the inferior alveolar nerve and intraoral anatomy within clinically feasible scanning times using specific surface coils and the interference of dental implants and inferior alveolar nerve using MRI (Flügge et al, 2016; Gradl et al, 2017; Kreutner et al, 2017; Wanner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, one should keep in mind that the "misjudgment" might actually not necessarily occur when judging the MRI images. In fact, MRI is the most commonly used technique to directly visualize the IAN [22] and to precisely localize the IAN including pathologic processes [9,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, a VIBE sequence has been used to depict NVBs. [12][13][14] Several studies employed spin echo sequences, 15,16 but they have not more effectively depicted NVBs. Hence, in some cases, a clinician must potentially remove the metals causing a metallic artefact owing to the clinical requirements for identifying the MC.…”
Section: Figurementioning
confidence: 99%